Organophosphate Poisoning Simulation Case - Jessica Brooks; Amy Zosel; Britney Anderson (Association of American Medical Colleges, 2010)
Abstract This simulation case is intended for medical students and residents in emergency medicine and involves a patient that was exposed to organophosphates while working on a farm. While not a common problem seen in emergency departments in the United States, globally, pesticide poisoning remains one of the leading causes of death from suicide, and accounts for about 1/3 of suicides worldwide. Unintentional toxic exposure to organophosphates is uncommon. However, organophosphate poisoning should be considered in the appropriate clinical scenario. Organophosphates have traditionally been used in pesticide formations, and can be quickly absorbed through the skin, respiratory tract, and GI tract. The scenario reviews identification of organophosphate poisoning by clinical exam and history, and the management of this toxicological emergency. This simulation case provides an opportunity for medical students, residents, and even attending physicians to learn about the management of organophosphate poisoning in a life-like scenario. Organophosphate poisoning is an uncommon clinical presentation, and simulation will provide a safe way for participants to learn how to manage this toxicological emergency.